Increased Revenue From Averted Missed Appointments Following Telemedicine Adoption at a Large Federally Qualified Health Center - Omolola E. Adepoju; Tracy Angelocci; Omar Matuk-Villazon (SAGE Publishing, 2022)
This study examined savings from averted missed appointments following telemedicine adoption. Data were obtained from a large Federally Qualified Health Center in Texas during the early pandemic months. Patient encounters fell into one of three categories: (1) in-person visit, (2) telemedicine alone with no support team engagement, and (3) telemedicine with previsit support team engagement for device and connectivity testing. Our findings revealed that in-person visits had a 21% missed appointment rate compared to 19% for telemedicine alone and 15% for telemedicine with previsit support. Translating the reductions following both telemedicine encounters into net reimbursement, telemedicine alone saved the Federally Qualified Health Center $16 444 per month, while telemedicine + support team reduced missed appointments and saved the clinic an additional $29 134. The revenue from averted missed appointments totaled $45 578 per month. In conclusion, telemedicine reduced missed appointments, and these averted missed appointments translated into cost-savings. Savings were more pronounced with the implementation of a support team that conducted previsit device and connectivity testing.